Analisis Penentuan Biaya Produksi Air pada Perusahaan Umum Daerah Air Minum (PERUMDA) Tirta Bantimurung di Kab.Maros (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to identify and analyze the determination of water production costs at the Regional Public Water Company (Perumda) Tirta Bantimurung in Maros Regency. The variables in this study consist of a single variable that focuses on the determination of water production costs. The population in this study is all documents related to water production costs at PERUMDA Tirta Bantimurung in Maros Regency. The sample in this study used purposive sampling. The data collection techniques used are interviews and documentation. Data analysis is conducted qualitatively, which consists of data reduction, data presentation, and drawing conclusions. The results of the research show that based on the results of research on the Analysis of Determining Water Production Costs at the Regional Public Company for Drinking Water (PERUMDA) Tirta Bantimurung in Maros Regency, the conclusion drawn in this research is that the determination of water production costs at PERUMDA Tirta Bantimurung in Maros Regency is not in accordance with theory. because the cost classification is still combined into all components of direct raw material costs, direct labor costs and factory overhead costs. In determining the costs, we use water source costs, water processing costs, and transmission/distribution costs. These three costs always increase every year (2020-2022)